Ética en las relaciones laborales en tiempos de globalización - Armando J., Camejo (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
In the present test the paper of the ethics in the labor relations in the days of globalization In this analysis is analyzed stands out some general considerations of the problem characterized by the phenomenon of the globalization as motor axis of those new values and that new ethics of the work based on a new form of accumulation marked by the consumption in the emergent capitalist system, that it consists of the application of the knowledge to the same knowledge.